Strategi Keberhasilan Penurunan Emisi Gas Rumah Kaca Di Singapura: Inspirasi Untuk Indonesia - Marshanda, Sherly; Feriyani, Feriyani; Khairani, Siti (Universitas Multi Data Palembang, 2025)
Recently, the world is facing the climate change. Therefore, government in various countries have been attempting to make a policy to control the climate change, such as the carbon tax policy. In Indonesia, however, tax carbon is still a discourse. Therefore, it is essential to know the successful strategy of implementing carbon tax in countries that have implemented it, such as Singapore, so that it could effectively be implemented. This research aims to analyze the successful strategy taken by the Singapore government to apply the carbon tax policy. This research uses the literature review method, with the help of journals, e-book, as well as online resources on the internet. The result shows that Green House Gases (GHG) in Singapore has dramatically decreased to 80% by 2022. Hopefully, this research could inspire Indonesia’s government to adopt the strategy used by the Singapore’s government in respond to minimize the GHG.